La internet como herramienta de investigación en psicología (Revista Puertorriqueña de Psicologia, 2016)
The internet has made available a wealth of information and resources which can significantly transform and improve the careers of psychologists and other mental health professionals. However, in order to maximize the benefits of the new communication and information techonologies it is necessary for these professionals to have a clear understanding of the tools which are now available, as well as the most convenient ways in which to use them. The present article is an introduction, especially designed for psychologists, to the internet and related technologies. It contains a brief historial background which describes how the internet was created and how it functions. It then describes communication technologies, sucha as e-mail, chats, discussion forums, and lists, among others, explaining what they are, how they can be used, and where to obtain them for free on the WWW. The article also deals with how to effectively perform search engines and providing useful strategies for obtaining accurate results. Futhermore, the article provides guidelines for critically evaluating the quality of the information obtained on the web, and includes a comprehensive list of the best psychology related resources available on the WWW.